Evaluating the impact of loneliness and social isolation on health literacy and health-related factors in young adults - Vasan, Shradha; Eikelis, Nina; Lim, Michelle H.; Lambert, Elisabeth (Frontiers in Psychology, 2023)
Objectives. In current study, we aim to extend previous research by investigating the unique impact of loneliness on health literacy and health-related factors of young adults, after controlling for social isolation, depressive symptomology, and social anxiety, as well as evaluate how social isolation and loneliness differ in their impact on health literacy, and health-related factors among young adults, after accounting for abovementioned concomitant variables. Methods. Using a cross-sectional study design, 521 young adults completed an online survey in 2020, where they self-reported their loneliness, social isolation, health-related factors, and health literacy data. Results. Increased loneliness was associated with decrease in several health literacy domains (e.g., poorer social support for health, lower appraisal of health information, among others) and increase in some health-related factors (e.g., higher perceived stress, higher negative affect), among young adults, even after controlling for social anxiety, depressive symptomology, and social isolation. Contrastingly, increase in social isolation was associated with changes in some health-related factors - more somatic health complaints, higher alcohol use, poorer cognitive and physical functioning, and lower scores for only one health literacy domain (i.e., social support for health) among young adults, after adjusting for the influence of social anxiety, depressive symptomology, and loneliness. Conclusions. Even after accounting for the influence of several co-occurring social and mental health symptoms, higher loneliness was associated poorer health literacy and health-related factors in young adults. We also found loneliness and social isolation may differ in the mechanisms through which they impact health literacy and health-related factors in young adults.